Stingray: Epidemiological and Clinical Aspects. Bolívar State, Venezuela - Julman R Cermeño; Julmery J Cermeño; Nilio Salazar; Norka Gómez de Salazar (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
Sstingrays are poisonous fish that can produce lesions by means of injecting poison to the victim through a penetrative structure. The aim of this study was to determine the prevalence of stingray poisoning in the Ruiz y Páez Hospital, the principal hospital in Bolívar state. It was a descriptive, retrospective study. We reviewed data as to stingray poisoning cases during the period between January 1996 and July 2003. Twenty-four cases were registered (3.8 cases / year). Mean age of those affected was 26.2±16.1 years, 91.7% were masculine. The most frequent occupations were: fishermen (33.3%), students (25%) and farmers (16.7%), and 70.8% came from Bolivar State. The wounds were located in the lower members in all the cases, with local pain (100%), erythema (91.6%), hemorrhage (41.6%), necrosis and ulceration (29.2%). All patients were treated with asepsis and antisepsis of the wound, only 33.4% required surgical cleaning of the wound. All evolved satisfactorily. Poisoning by stingrays constitutes a reality in the Bolívar state, and the physicians that serve this region have to see to this problem and to prepare to adequately manage it.